2018
DOI: 10.1002/ddr.21441
|View full text |Cite
|
Sign up to set email alerts
|

Actinomycin‐D and dimethylamino‐parthenolide synergism in treating human pancreatic cancer cells

Abstract: Pancreatic cancer is the third leading cause of death in the US with a poor 5-year survival rate of 8.5%. A novel anti-cancer drug, dimethylamino-parthenolide (DMAPT), is the water-soluble analog of the natural sesquiterpene lactone, parthenolide. The putative modes of action of DMAPT are inhibition of the NFκB pathway and depletion of glutathione levels; the latter causing cancer cells to be more susceptible to oxidative stress-induced cell death. Actinomycin-D is a polypeptide antibiotic that binds to DNA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…This inhibition is thought to be due to its gamma methylene lactone which probably alkylates the proximal thiolate of Cys 1226 of the catalytic domain ( Liu et al, 2009a ). Recently, a new parthenolide derivative, dimethylamino-parthenolide, has been reported to inhibit the Nuclear chain factor kappa‐light‐chain enhancer of activated B cells (NF-κB) pathway and causes depletion of glutathione levels; the latter causing cancer cells to be more susceptible to oxidative stress‐induced cell death ( Pei et al, 2009 ; Lamture et al, 2018 ). This result highlights the potential role of this drug as a chemopreventive agent and in epigenetic cancer therapy.…”
Section: Dna Methyltransferases Inhibitors ( Figure 1 mentioning
confidence: 99%
See 1 more Smart Citation
“…This inhibition is thought to be due to its gamma methylene lactone which probably alkylates the proximal thiolate of Cys 1226 of the catalytic domain ( Liu et al, 2009a ). Recently, a new parthenolide derivative, dimethylamino-parthenolide, has been reported to inhibit the Nuclear chain factor kappa‐light‐chain enhancer of activated B cells (NF-κB) pathway and causes depletion of glutathione levels; the latter causing cancer cells to be more susceptible to oxidative stress‐induced cell death ( Pei et al, 2009 ; Lamture et al, 2018 ). This result highlights the potential role of this drug as a chemopreventive agent and in epigenetic cancer therapy.…”
Section: Dna Methyltransferases Inhibitors ( Figure 1 mentioning
confidence: 99%
“…This result highlights the potential role of this drug as a chemopreventive agent and in epigenetic cancer therapy. Recently, it has been demonstrated that combination of the anticancer drug actinomycin-D, which functions by intercalating into DNA, and dimethylamino-parthenolide results in a synergistic inhibition of Panc‐1 pancreatic cancer cell growth ( Lamture et al, 2018 ). However, the potential clinical use of parthenolide is still not clear.…”
Section: Dna Methyltransferases Inhibitors ( Figure 1 mentioning
confidence: 99%
“…Lung cancer Preclinical December 3, 2019 AD has hepatoxicity, and TS is without toxic side effects in nude mice [29,30] signaling pathway in preclinical experiments. For example, XAV939 can inhibit β-catenin signaling and thus attenuate CSC progression by interacting with the terminal anchor polymerase-binding domain (TBD) in Axin [40], which can abrogate CSC-mediated chemoresistance in head and neck squamous cell carcinoma (HNSCC) and colon cancer cells [41,42].…”
Section: Wnt Signaling Pathway Inhibitorsmentioning
confidence: 99%
“…A phase 2 clinical trial has shown that actinomycin-D could be an effective drug in the pancreatic cancer treatment; however, it has substantial dose-limiting toxic side effects [167]. Actinomycin-D combined with DMAPT synergistically enhanced cell death of pancreatic cancer cells and may provide an effective treatment at lower doses [168].…”
Section: Parthenolide Combined With Other Drugsmentioning
confidence: 99%